Translanguaging Dynamics in Non-Native English Classrooms - Acharya, Ramji (Journal of NELTA Koshi (JoNK), 2024)
This research investigates the pragmatic applications of code-switching employed by English language instructors in the pedagogical context, aiming to discern its role during interactions within the English teaching and learning process. The study, conducted in Lalitpur across three educational institutions, observed over 15 classes taught by five different educators. Utilizing interpretive ethnography within a qualitative research paradigm, the methodological framework involved meticulous observation, audio-visual recordings, and subsequent transcription for data collection and analysis. The findings revealed that code-switching in the English as a Foreign Language (EFL) classroom serves as a facilitative tool for enhancing interactions during the learning process. The identified purposes of code-switching by teachers during instructional activities include clarification, reiteration, explanation, inquiry, translation, assessment of comprehension, emphasis on linguistic elements, inferential communication, vocabulary development, facilitation of class discussions, provision of feedback, support for memorization, classroom management, and entertainment.